2018
DOI: 10.1002/jbm.a.36578
|View full text |Cite
|
Sign up to set email alerts
|

Biological applications of phytosynthesized gold nanoparticles using leaf extract of Dracocephalum kotschyi

Abstract: In this work, biosynthesis potentials of Dracocephalum kotschyi leaf extract for the production of gold nanoparticle (AuNPs) were studied, and the biological (catalytic, antibacterial, antioxidant, and anticancer) activities of studied AuNPs were evaluated. Different analytical techniques including UV–visible spectroscopy, X‐ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), scanning electron microscope (SEM), energy dispersive X‐ray analysis, and transmission electron microscopy (TEM) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 74 publications
(163 reference statements)
0
13
0
Order By: Relevance
“…Our previous study on antibacterial effects of AgNPs synthesized by Nigella arevensis leaf extract with mostly spherical shape and size‐range of 5–100 nm [ 23 ] showed the inhibition zone of 17 mm and MIC value of 7.82 μg mL −1 for E. coli , which are significantly weaker than our finding in the current study. In another study, we showed that gold nanoparticles synthesized by D. Kotschyi leaf extract also have significant antibacterial effects against B. subtilis , [ 22 ] indicating that D. Kotschyi leaf extract has a synergistic impact on antibacterial effects of NPs. D. Kotschyi leaf extract mediated NPs have better antibacterial effects comparing to similar NPs from different sources.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous study on antibacterial effects of AgNPs synthesized by Nigella arevensis leaf extract with mostly spherical shape and size‐range of 5–100 nm [ 23 ] showed the inhibition zone of 17 mm and MIC value of 7.82 μg mL −1 for E. coli , which are significantly weaker than our finding in the current study. In another study, we showed that gold nanoparticles synthesized by D. Kotschyi leaf extract also have significant antibacterial effects against B. subtilis , [ 22 ] indicating that D. Kotschyi leaf extract has a synergistic impact on antibacterial effects of NPs. D. Kotschyi leaf extract mediated NPs have better antibacterial effects comparing to similar NPs from different sources.…”
Section: Resultsmentioning
confidence: 99%
“…The infusion was cooled, centrifuged, and filtered by filter paper to get a transparent aqueous extract, then stored at 4 °C for further use. [ 22 ]…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a lot of information available in the literature regarding the molecular targets underlying the anti-tumor properties of biocompatible GNPs [21,22]. GNP-based plants have been experimentally documented to possess medicinal properties as well as various biological properties such as antioxidant, anti-bacterial, anti-inflammatory, and anti-tumor activities [23][24][25]. Cudrania tricuspidata is a perennial plant of the Moraceae family, which is mainly distributed in Asian countries such as Korea, China, and Japan.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these important properties, there are also studies emphasizing the in vitro or in vivo toxic effects of AuNPs, synthesized especially by means of chemical procedures (Gerber, Bundschuh, Klingelhofer, & Groneberg, ; Jia, Ma, Wei, & Qian, ; Xia et al, ). The so‐called “green synthesis” methods involving biological macromolecules, such as silk fibroin (Jia, Guo, Zhu, & Ma, ), chitosan (Yang & Li, ), and leaf extracts (Chahardoli, Karimi, Fattahi, & Salimikia, ) have been introduced recently to alleviate the toxicity‐related problems as well as to improve the colloidal stability of AuNPs. There is also no need to use potentially toxic reducing and/or stabilizing agents for the synthesis reactions since biological macromolecules could act as both reducing and stabilizing agents (Jia et al, ; Yang & Li, ).…”
Section: Introductionmentioning
confidence: 99%